Migrations of Philosophizing Jews and Jewesses in the Second Polish Republic - Smywińska-Pohl, Anna (Sensus Historiae, 2021)
The article’s subject is a migration of Jewish students who received doctorates in rigorous philosophy at some Polish universities in the years 1918–1939. I analyze the geographical origin of students (understood primarily as the place of birth) as well as reasons for their choosing a specific university (Jagiellonian University, University of Jan Kazimierz and University of Warsaw). Moreover, I present migrations between academies during studies and - if it was possible to determine the details - after receiving the diploma. The issues are discussed in the context of the education level in Poland and problems related to obtaining a higher degree in the years 1918–1939.